2019
DOI: 10.1590/s1677-5538.ibju.2019.0330
|View full text |Cite
|
Sign up to set email alerts
|

Serving as a bedside surgeon before performing robotic radical prostatectomy improves surgical outcomes

Abstract: Introduction: To evaluate the influence of previous experience as bedside assistants on patient selection, perioperative and pathological results in robot assisted laparoscopic radical prostatectomy. Materials and Methods: The first 50 cases of two robotic surgeons were reviewed retrospectively. Group 1 consisted of the first 50 cases of the surgeon with previous experience as a robotic bedside assistant between September 2016-July 2018, while Group 2 included the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Despite that, surgeons involved in this study overcame their learning curve with a standardized protocol and similar methods. They were included at the robotic program after assisting cases as bedside surgeons (24), completing the training on da Vinci system, and after approval of the head of the department. Some of them have a huge previous experience in open procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, surgeons involved in this study overcame their learning curve with a standardized protocol and similar methods. They were included at the robotic program after assisting cases as bedside surgeons (24), completing the training on da Vinci system, and after approval of the head of the department. Some of them have a huge previous experience in open procedures.…”
Section: Discussionmentioning
confidence: 99%
“… 16 According to Cimen, prior practice as bedside surgeon let the console surgeon reach better surgical outcomes for radical prostatectomy. 17 …”
Section: Discussionmentioning
confidence: 99%
“…16 According to Cimen, prior practice as bedside surgeon let the console surgeon reach better surgical outcomes for radical prostatectomy. 17 To go into more details, Sheridan et al estimated that a surgeon should only operate from the console after 20 procedures as bedside surgeon, 11 whereas Winder et al suggested 10 procedures as threshold in their training program. 16 This is in keeping with our results, 73% of the respondents reporting that they would feel confident after 5 to 10 interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as the experience of bedside assistants increased, the bedside assistants became familiar with the operative setting and learned more from watching cases. [ 27 ] Cimen et al [ 28 ] indicated that previous bedside assistant experience enhanced troubleshooting skills. Xu et al [ 29 ] reported that, in addition to individual surgeon experience, team familiarity contributed to reductions in operative times.…”
Section: Discussionmentioning
confidence: 99%